Analysis of Inflation and Rupiah Exchange Rate on Mudharabah Savings at Sharia Commercial Banks - wati, Mesis Rawati; Wewis Gilang Sari; Febri Rahmita; Selvi Purwaningsih; Herliza Agustin; Yolanda Effendi; Siti Aisyah; Ridha Fauzana; Tisa Amelia; Rayzul Hawari; Andriawan; Awaluddin (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
Inflation is one of the macroeconomic symptoms associated with a decline in the exchange rate (money). Inflation has always been a heated topic of discussion in various economic circles. This indicates that the effects of the economic crisis depend on the nature of each group's income and fortune. The condition is severe if the income is stable or rising but less than the inflation rate. Their material well-being improves if their income grows faster than the inflation rate. This study examines the impact of inflation and the rupiah exchange rate on Islamic banking Mudharabah savings. The data utilized are time series data from the Sharia Banking Statistics Report and the Central Statistics Agency (BPS) published by Bank Indonesia. This research method falls under the category of library research, namely searching for research data or information by reading scientific journals, reference books, published financial statements, and other library-accessible support materials for this paper. The findings of this study indicate that the variables Inflation and Exchange Rate have a significant effect on Mudharabah Savings simultaneously.